Three-Month Iron Supplementation as Treatment for Microcytic Hypochromic Anemia in Pregnancy - Donel Donel; Dhini Aiyulie Novri; Ruza Prima Rustam; Maya Savira (Majalah Kedokteran Bandung, 2021)
In pregnant women there is a twofold increase in iron requirements due to increased blood volume without the expansion of plasma volume. Pregnant women are very prone to suffering from iron deficiency anemia. Iron deficiency anemia generally has an erythrocyte index which represents  hypochromic microcytic. This study aimed to determine the effect of three-month iron tablet supplementation as a therapy against microcytic hypochromic anemia in pregnancy. This was a quantitative quasi-experimental study using pre-test and post-test design. The study was conducted in May-September 2020 at the Arifin Achmad Regional General Hospital, Riau Province, Indonesia. Subjects were 30 pregnant women with microcytic hypochromic anemia. Primary data were analyzed using statistical paired sample t-tests. Results showed that there was an increase in hemoglobin levels after the supplementation of iron tablet from an average of 9.1 ± 1.2 gr/dl to 11.8 ± 1.0 g/dl. This change was significant based on the results of the T-test (p-0.003) Thus, iron supplementation for three month significantly increases hemoglobin levels in pregnant women.